Temporal bone findings in trisomy 18 and 21 syndromes - Chrobok, V; Simáková, E (European archives of oto-rhino-laryngology, 1997)
The temporal bones from fetuses with known autosomal trisomy syndromes were examined histopathologically after spontaneous or induced abortions. Fetal ages dated from the 17th to the 24th week of pregnancy. In all, 17 temporal bones from nine fetuses were studied and included seven cases of Down's syndrome and two of Edwards' syndrome. Temporal bones from fetuses with Down's syndrome had more abnormalities of the external and middle ears than of the inner ear. The bones from the fetuses with Edwards' syndrome showed abnormalities of the external or middle ear and retarded development of the inner ear (failed ossification of the otic capsule and unformed organ of Corti).
Keywords: Trisomy; těhotenství; Down Syndrome; trizomie; Humans; Downův syndrom; gestační stáří; ucho; Temporal Bone; mužské pohlaví; Gestational Age; Abortion, Eugenic; Infant, Newborn; novorozenec; ženské pohlaví; Chromosomes, Human, Pair 18; lidé; Pregnancy; potrat eugenický; Ear; Male; spánková kost; lidské chromozomy, pár 18; Female